KEANEKARAGAMAN JENIS PRIMATA DI SEKSI WILAYAH II SEMITAU TAMAN NASIONAL DANAU SENTARUM KABUPATEN KAPUAS HULU - Kinantono, Hendri; Budhi, Setia; Ardian, Hafiz (Universitas Tanjungpura, 2018)
Primates are considered very importance since they can help forest regeration that can also be an indicator ofÂ forest health. Health population in the forest areas also suggest the possibility of other species of animals that is also still present in a considerable number. This reschearch was conducted in the management section of the Region ii Semitau of Sentarum National Park Kapuas Hulu. This study aims to reveal the existing primate diversity and population in each group. This research was conducted from December 2014 using a survey method with a transect of 1000 meters long 100 meters wide as a sample unit. The results show that the number of primates found was as many as 145 individuals consisting of 3 (three) species. These species are orangutan (Pongo pygmaeus), probscis monkey (Nasalis larvatus), long-tailed macaque (Macaca fascicularis). Species diversity index value was 0.8594; Evenness index value was 0.7821; Dominance index value was 0.4649 and species richness index value was 2.1613.Keywords: Kapuas Hulu, National Park, Population, Primates, Sentarum Lake, Species Diversity